2014
DOI: 10.1007/s10611-013-9506-2
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and corruption: a complex relationship

Abstract: We argue that an 'electoral democracy' is not sufficient to reduce corruption. Our contention is that the institutions associated with mature democracy are crucial to successfully deterring corrupt behaviour. At the core of our argument is the idea that with well-functioning institutions, the probability of detection and punishment is sufficiently high to deter most decision makers from choosing to act corruptly. The empirical evidence we present supports this idea. The nonlinearity of democracy variables is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
1
16
0
2
Order By: Relevance
“…Una reciente investigación (Saha, Gounder, Campbell, & Su, 2014) argumenta que la democracia electoral por sí sola no es suficiente para reducir los niveles de corrupción, entretanto, los mecanismos institucionales propios de democracias más desarrolladas son pivotes que sirven de barrera al comportamiento corrupto. Estas democracias tienen instituciones que funcionan mejor, donde los posibles corruptos son más fácilmente detectados lo que encarece el costo de la relación de corrupción.…”
Section: Resultsunclassified
“…Una reciente investigación (Saha, Gounder, Campbell, & Su, 2014) argumenta que la democracia electoral por sí sola no es suficiente para reducir los niveles de corrupción, entretanto, los mecanismos institucionales propios de democracias más desarrolladas son pivotes que sirven de barrera al comportamiento corrupto. Estas democracias tienen instituciones que funcionan mejor, donde los posibles corruptos son más fácilmente detectados lo que encarece el costo de la relación de corrupción.…”
Section: Resultsunclassified
“…Sung (2004) found that corruption level is a cubic function of current democracy level. Saha et al (2014) found the relationship between current democracy level and corruption was significant only if the democracy level reached a specific threshold.…”
Section: Democratic Traditionmentioning
confidence: 95%
“…However, this link is not as straightforward as it seems. Most authors emphasize that an “independent effect of democracy is dubious” (Paldam, 2002: 238) and only a “mature democracy is crucial to successfully deterring corrupt behavior” (Saha et al, 2014: 287). Thus, Daniel Treisman brings to the fore, in the context of anti-corruption measures, the problem of “endogeneity of democracy”: “[…] the relationship between democracy and lower corruption may reflect that corrupt officials stifle democracy rather than that exposure to democracy reduces corruption” (2000: 435).…”
Section: Anti-corruption Discourse Through the Lens Of Governmentalitmentioning
confidence: 99%